Secondary Childcare in the ATUS: What Does It Measure? - Jay Stewart; Mary Dorinda Allard (Institute for the Study of Labor (IZA), 2015)
Unlike most of the earlier U.S. time-use surveys, the American Time Use Survey (ATUS) does not collect information on secondary activities. It does, however, include a set of questions asking respondents to identify times when a child under 13 was "in your care." The goal of these questions is to measure the amount of time that respondents spend looking after children while doing something else. The respondent need not be actively engaged with the child, but must have a general idea of what the child is doing and be available to help if necessary. Although questions similar to these have been asked for a number of years in the Statistics Canada time use survey, very little research has been conducted to assess the quality of these data. This paper investigates whether the secondary childcare questions in the ATUS are measuring the stated concept. We look for inconsistencies in the data and examine certain, potentially problematic, reporting patterns. We also construct alternative estimates that exclude time spent in secondary childcare that is inconsistent with other data collected during the interview and find that the ATUS measure overestimates secondary childcare by at most 5 percent or about 16 minutes per day.
Keywords: C83; J13; J22; 330; survey methods; childcare; time use